Identidades profissionais e identificação organizacional: estudo com profissionais de saúde de um hospital público de Belo Horizonte - Juliana Goulart Soares do Nascimento (2012)
The Organization exerts a relevant significance to the social construction of the identity of individuals who work in it, for this reason. This research investigated the process of l organizational identification and the professional identities of doctors, nurses and medical i technicians services in a full service hospital by Sistema Unico de Saude (SUS) - the Brazilian single health system - located in Belo Horizonte. The study was descriptive character and a qualitative approach was adopted, in which it was used the case study method, that by means of thirty emi-structured interviews later submitted to a content analysis i provided the results here discussed. It was observed that interviewed doctors build their professional identities through elements such as status, idealism, responsibility, dedication,i competence, long working hours, help to patients and link with education and research; nurses build their professional identities from the desire to take care of people, ethics, humanity, responsibility, care and management processes; the technicians have as fundamental identity traits the care, serve, dedication and responsibility. These constructions of their professional identities interfere with levels of identification with the organization. Thus, while doctors and , nurses display low levels of identification with the organization and high levels of i identification with their careers, the technicians present higher level of organizational identification, including superidentification factors. ln this way, through the understanding that the commitment to SUS, the interdisciplinarity of work, social responsibility, educationand research, as well as the assistance are factors that promote the organizationalidentification; and that the devaluation of labour and the lack of transparency in management are factors of disidentification, offers rich elements to the hospital human resource management so they can assess employee perceptions and schedule changes that they understand as needed to a bigger and better identification of these professionals with the same.